EXPLORING ISLAMIC PEER-TO-PEER LENDING FOR THE UNBANKABLE - Rizqi Umar Al-Hashfi; Alyta Shabrina Zusryn (Airlangga International Journal of Islamic Economics and Finance, 2019)
Increasing internet penetration and technology-savvy generation in Indonesia can be an opportunity for high-tech businesses. Those are driven by the significant growth in the number of borrowers and lenders at the peer-to-peer (P2P) marketplace that provides alternative funding for small and medium enterprises (SMEs). The presence of shariacompliant P2P providers offers alternatives for both borrowers and financiers who concern about Islamic values. Our work aims to discuss the role of sharia P2P lending on improving people's welfare in Indonesia. By observing 26 P2P platform providers, we conclude that the sharia P2P providers are the potential to be developed. The applications of Islamic value technological advancements, which are the prohibition of interest, transparency, and a sophisticated credit scoring system, enable the unbanked population to access financial service, especially lending. However, the sharia platforms do not offer the redemption mechanism for financiers who take their money back early. Therefore, we also propose an integrated scheme for sharia P2P platforms.